An awkward contaminant: are mercury concentrations in historically collected fossils a result of storage conditions? - Surmik, Dawid; Cabała, Jerzy; Balin, Katarzyna; Szade, Jacek (Geology, Geophysics and Environment, 2022)
High concentrations of mercury (Hg), reaching astonishing values in two cases, have recently been detected in Middle and Late Triassic fossil reptile bones, housed for over 100 years in several Polish museum collections. Since no correlation between either the life modes of these taxa or their burial environment was observed, the studied contaminations seem to be associated with housing conditions. The specimens were kept for an extended amount of time in boxes, in which they were stored soon after finding. A proximity of mercury-containing materials, like mercury fulminate, and unstandardized conditions of storage and conservation of the remains may result in contamination of porous bone with mercury. A detailed knowledge about the housing history of old museum collections has great importance to their prospective studies.